Pengetahuan dan Sikap Pasien terhadap Swamedikasi Pemilihan Obat Tradisional dan Konvensional di Apotek Dharma Medika Badung - Susianti, Luh; Megawati, Fitria; Agus Adrianta, Ketut (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
According to the World Health Organization (WHO), self-medication is choosing and using modern medicine, herbal medicine, or traditional medicine to reduce or overcome a disease or disease symptoms. The implementation of self-medication must be distinct from the use of traditional medicine and conventional medicine, where preferences for drug selection are greatly influenced by knowledge and attitude factors. This research aimed to determine the level of knowledge and attitudes toward choosing traditional and conventional medicines and self-medication in the Dharma Medika Badung Pharmacy patients. The research design used was observational descriptive, and the sampling technique was carried out using the accidental sampling method. A total of 68 respondents met the inclusion and exclusion criteria. The instrument in this research was a closed questionnaire with 14 questions, where the questionnaire's validity and reliability were first tested. The results showed that the level of knowledge of the respondents with